2018
DOI: 10.1177/0379572118761682
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Diversity and Growth of Children Under 24 Months of Age in Rural Dodoma, Tanzania

Abstract: Greater maternal dietary diversity was associated with improved child WHZ and WAZ outcomes. Sustainable interventions to increase maternal dietary diversity may improve WHZ and WAZ in young children in similar settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…Our analysis covers data from eight sites in six countries, including Kersa and Harar in Ethiopia; Dar es Salaam and Dodoma in Tanzania; Ningo Prampram in Ghana, Ibadan in Nigeria; Iganga and Mayuge in Uganda; and Nouna in Burkina Faso. Study site details are described in Berhane et al and other studies .…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis covers data from eight sites in six countries, including Kersa and Harar in Ethiopia; Dar es Salaam and Dodoma in Tanzania; Ningo Prampram in Ghana, Ibadan in Nigeria; Iganga and Mayuge in Uganda; and Nouna in Burkina Faso. Study site details are described in Berhane et al and other studies .…”
Section: Methodsmentioning
confidence: 99%
“…Dietary diversity score, which consists of a simple count of food groups that an individual has consumed over the preceding 24 h, is considered a proxy for nutrient adequacy of the diet of individuals [ 21 ]. Several studies in African countries have revealed that low dietary diversity was associated with malnutrition, while consumption of an adequate variety of food can improve general nutritional status [ 15 , 19 , 20 ]. In order to plan an effective intervention program aimed at improving feeding practices and dietary diversity of children living with HIV, it is crucial to understand their current nutritional status and dietary intake.…”
Section: Introductionmentioning
confidence: 99%
“…In the Infant and Young Child Feeding guidelines published by the United Nations, dietary diversity scores of pre-school children are dichotomized: children who had at least four of the seven food groups were considered to have adequately diversi ed dietary intake [29]. In our study, we dichotomized the score using median as there is no recommended cut-off points for our study population (school-age children) [16][17][18][19][20][21]. The median of the children's dietary diversity scores was calculated to determine the cutoff point between lower and higher dietary diversity.…”
Section: Data Management and Statistical Analysismentioning
confidence: 99%
“…Along with micronutrient supplementation, su cient dietary diversity is considered a key to improving overall nutritional and health status of children living with HIV [12][13][14]. A number of recent studies have explored risk factors for undernutrition, using dietary diversity score developed by the Food and Agriculture Organization [15][16][17][18][19][20]. Dietary diversity score, which consists of a simple count of food groups that an individual has consumed over the preceding 24 hours, is considered a proxy for nutrient adequacy of the diet of individuals [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation